Description of the larva of Ilyobius chilensis (McLachlan) (Megaloptera: Sialidae) and notes on the adult morphology - Archangelsky, Miguel; Pessacq, Pablo; Berrondo, Matias (Zootaxa, 2017)
Ilyobius chilensis (McLachlan) is reported from western Chubut Province, Patagonian Argentina. The first description of the larvae of this species is provided supported by illustrations. Morphological comparisons with other known sialid larvae are included. Additional notes and illustrations of adult morphology and behavior of this species are provided.